Downy Mildew Infection in Indonesian Melon Cultivar 'Melona' Based on Morphological and Anatomical Characters - Angellya, Bunga Finovel; Yusuf, Adib Fakhruddin; Wibowo, Wiko Arif; Daryono, Budi Setiadi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Melons are a horticultural crop of the Cucurbitaceae family with high economic value and worldwide distribution. The 'Melona' variety is the result of breeding selection from commercial melons in Indonesia and has a golden yellow skin color with lobes, crisp flesh, and a high degree of sweetness. Downy mildew is a fungal infection that attacks the leaves of the plant causing brownish-yellow-colored symptoms. Downy mildew can cause crop failure under extreme conditions as the plant loses its productive capacity. Infection levels were observed by scoring and calculating disease index scores. The morphology of healthy and diseased plants was documented and analyzed descriptively. Anatomical features of healthy and diseased leaves were compared using anatomical observations on leaf cross-sections. Quantitative data analysis was carried out using the T-test analysis method with a 5% significance level. Melona's resistance to downy mildew is in the tolerant to susceptible category. Chlorosis and necrotic spots on the leaves and stunted growth are symptoms of downy mildew infection. Healthy leaves had a greater axial and abaxial epidermal thickness, a lower mesophyll thickness, a smaller cell size and a better quantity and quality of trichomes than leaves infected with downy mildew.